Identifikasi Tumbuhan Bawah di Dusung pada Ketinggian Tempat yang Berbeda di Dusung Hative Besar, Kecamatan Teluk Ambon, Kota Ambon - Maria Mahubessy; Johan Riry; Elia Madubun (JURNAL PERTANIAN KEPULAUAN, 2022)
"Dusung" is a habitat with a variety of plant communities in the form of trees. bushes, and grass. Research aims to identify under growth in "Dusung" at different altitudes. The research was carried out in Dusung Hative Besar using the method of surveying weeds directly in the field. Vegetation analysis using the squared method by purposive sampling with sample plots measuring 1×1m. Sampling on nutmeg plantation areas is carried out in each area at various different heights, namely at altitudes of 0, 100, and 200 m asl. The results showed that the value of the community coefficient (C) obtained from the comparison between two communities, namely between 0 and 100 m asl, was 0%, while 0 and 200 m above sea level was3.17%. This shows that the lower plant communities at an altitude of 0 and 100 m above sea level and 0 and 200 m above sea level are different because of the value of C<70%. While the comparison between two communities altitudes of 100 and 200 asl has a C value of 72.48% means that the lower plant community between the two heights of the place being compared is the same or uniform (C >70%).